Relapsing Nephrotic Syndrome Associated with COVID-19 - Jusli Aras; Andi Utari Dwi Rahayu; Husein Albar (Cermin Dunia Kedokteran, 2022)
An 8-year and 2-month-old girl presented with generalized edema for two days with a mild cough and shortness of breath. She was diagnosed with a relapsing nephrotic syndrome (NS) and Community Acquired Pneumonia due to a COVID-19 infection. The patient was discharged with complete remission NS and repeated negative PCR for SARS-CoV-2 from nasopharyngeal swabs. It is important to consider COVID-19 infection as a likely trigger of relapsing NS in children. Seorang anak perempuan usia 8 tahun 2 bulan masuk rumah sakit dengan keluhan edema anasarka selama 2 hari disertai batuk ringan dan sulit bernapas. Diagnosis adalah sindrom nefrotik relaps, pneumonia COVID-19, dan malnutrisi. Pasien dipulangkan setelah sindrom nefrotik remisi dan hasil PCR SARS-CoV-2 negatif. Infeksi COVID-19 penting dipertimbangkan sebagai pencetus relaps sindrom nefrotik.